2016
DOI: 10.1016/j.jfma.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of lipid metabolism gene SAR1 homolog B and the risk of Alzheimer's disease and vascular dementia

Abstract: SAR1B polymorphisms were associated with AD risk; results were not significant after correction for multiple tests. Simultaneous screening using SAR1B rs11948613 and ApoE ε4 status offered a better sensitivity for AD screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Accumulating evidence has demonstrated that genes encoding certain endocytosis-related proteins are the targets of chromosomal rearrangement in human hematopoietic malignancies, and abnormal expression or mutations of these proteins have been reported in human cancer, suggesting a potential link between endocytosis proteins and cancer (36). SAR1B is a GTPase that serves a key role in the exportation of proteins from the ER to the Golgi apparatus by recruiting β-COP to the ER and promoting vesicular transport (10,37,38). Considering the essential function of lipids in cancer, it is possible that SAR1B may affect the molecular mechanisms involved in cell proliferation or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that genes encoding certain endocytosis-related proteins are the targets of chromosomal rearrangement in human hematopoietic malignancies, and abnormal expression or mutations of these proteins have been reported in human cancer, suggesting a potential link between endocytosis proteins and cancer (36). SAR1B is a GTPase that serves a key role in the exportation of proteins from the ER to the Golgi apparatus by recruiting β-COP to the ER and promoting vesicular transport (10,37,38). Considering the essential function of lipids in cancer, it is possible that SAR1B may affect the molecular mechanisms involved in cell proliferation or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CADASIL and HCHWA are the only known high‐penetrance genetic causes for small vessel VaD. Existing evidence thus far support the notion that most small vessel VaD is a product of genetic predisposition and environmental interaction. Hypertension is one such important environmental risk factor.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Despite years of intensive research, the link between hyperlipidemia and AD has yet to be established, although it has previously been suggested that genes regulating lipid metabolism may also be important in AD (11). Proprotein convertase subtilisin/kexin type 9 (PCSK9) encodes a protein formerly termed neuronal apoptosis-regulated convertase-1, a proprotein convertase belonging to the subtilase subfamily (12).…”
Section: Introductionmentioning
confidence: 99%